Manufacturing phobias: the political production of fear in theory and practice - Ramadan, Hisham M.; Shantz, Jeff (University of Toronto Press, 2016)
"Fear is a powerful emotion and a formidable spur to action, a source of worry and--when it is manipulated--a source of injustice. Manufacturing Phobias demonstrates how economic and political elites mobilize fears of terrorism, crime, migration, invasion, and infection to twist political and social policy and advance their own agendas. The contributors to the collection, experts in criminology, law, sociology, and politics, explain how and why social phobias are created by pundits, politicians, and the media, and how they target the most vulnerable in our society. Emphasizing how social phobias reflect the interests of those with political, economic, and cultural power, this work challenges the idea that society's anxieties are merely expressions of individual psychology. Manufacturing Phobias will be a clarion call for anyone concerned about the disturbing consequences of our culture of fear."--